DETERMINANTS OF ORGANIZATIONAL PERFORMANCE IN THE BANKING SECTOR: A LITERATURE REVIEW - Anggraini, Astriana; Gandawari, M. Agif; Aflal, Rauzatul; Nadila, Fitriatun (LPPM Universitas Malikussaleh, 2025)
The global banking sector faces major challenges in improving organizational performance, especially in the face of technological change, consumer behaviour, and evolving market conditions, therefore, it is important to understand the factors that influence bank performance, to improve operational effectiveness and competitiveness This study aims to identify the main factors that influence organizational performance in the banking industry in several countries. This study adopted the literature research method by analysing 10 relevant scientific articles from 20 selected articles. The analysis focuses on organizational culture, intellectual capital, leadership, and strategic characteristics. Organizational performance in the banking sector is influenced by internal factors such as organizational culture, intellectual capital, leadership style, and strategic attributes, as well as external factors such as national culture and market conditions. Organizational culture that supports collaboration and innovation, and culturally appropriate leadership, contributes significantly to improving bank performance. Innovative organizational culture, efficient intellectual capital management, strategic attributes, and participative leadership contribute significantly to improving bank performance. These strategies need to be adapted to the national cultural context to ensure the sustainability of the banking sector.